Development of a Universal Correctional Psycho-Acoustic Method for Optimizing the Human Functional State - A. Nazarova, K.; E. Milchakova, N. (International Journal of Engineering and Technology, 2018)
The purpose of this article is to substantiate the developed complex of musical means of influencing functional state of a person, presented in the form of â€œSimulator for Active Music Therapyâ€ (SAMT) methodology. This is a new psychocorrectional tool used for the development of conditioned reflex, cause-effect relationships, higher mental functions and the formation of functional comfort. From point of view of the system-structural approach, the theoretical and methodological foundations of correctional method are presented, and also modern conceptual approaches to the study of musical psychophysiology are considered.Â